(untitled) (Legal journal - Research in Legal and Social Sciences, 2020)
The new century amazes with a progressive technological advance in a globalized world, due to the criminal organizations’ fast adjustment to the sofisticated financial operations to launder ill-gotten funds and to try to legitimate all kinds of funds of dubious origin. After using solid tools of financial analysis and information crossover, it was possible to discover a new laudering technic, namely a check deduction that enables to hide the money trail, going unnoticed by the financial and supervisory bodies, situation that will lead to a capitalization of firmas that belong to the person under investigation. The money laundering is a major problem that undermines not only one nation, but the whole world, since it carries corruption as a direct consequence, distorts political and economical decisions, threatens the integrity of the State institutions, the financial entities and keeps the social ethic abducted. In this sense, this paper exemplifies, according to the analyzed casuistry the methods that are used in Paraguay for the cover-up operations that have illicit activities of Assets Laundering and Financing of Terrorism as origins of the funds.